Binder free and free-standing electrospun membrane architecture for sensitive and selective non-enzymatic glucose sensors. Issue 52 (10th June 2015) - Raj kumar, T.; Babu, K. Justice; Yoo, Dong Jin; Kim, Ae Rhan; Gnana kumar, G.
<x xml:space="preserve">Abstract</x> Novel free standing and binder free non-enzymatic electrochemical sensors were fabricated using in situ grown copper (Cu) nanoparticles on polyvinylidenefluoride-co-hexafluoropropylene (PVdF-HFP) nanofibers.